The dynamics of military students’ professional self-identification - Rudzenkou, Dzmitry U. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article deals with the issues of cadets’ professional self-identification in a military educational establishment. The theoretical basis of the study is the normative model of self-identification built according to the conceptual tradition of cultural-historical approach in psychology. The results of the research carried out in the educational establishment «Military Academy of the Republic of Belarus» are presented. The peculiarities of dynamics of military students’ professional self-identification are revealed and analysed. The process of professional self-identification is characterised by uneven development. The development dynamics of the professional self-identification structural components also has specific features. The dynamics of professional self-identification is strongly connected with the educational process and is individual due to the personal characteristics of the cadet.